Evaluating Medical Students' Perspectives on the CBME Curriculum: A Qualitative Exploration of Curriculum Structure, Pedagogical Approaches, and Educational Integration - Amit Kumar Kamboj; Mudit Sharma; Rashmi Ramanathan; Vivin Vincent; Jeevithan Shanmugam (National Board of Examinations Journal of Medical Sciences)
Introduction: The introduction of the Competency-Based Medical Education (CBME) curriculum by the National Medical Commission (NMC) in India in 2019 has reshaped medical education by integrating foundational courses, learning strategies, and assessment methods that emphasize competencies essential for modern healthcare. Unlike the traditional knowledge-centric model, CBME aims to produce well-rounded physicians equipped with clinical skills, ethical grounding, and communication abilities. This study aims to examine medical students' perspectives on the CBME curriculum, focusing on its foundational components, learning strategies, integration practices, and assessments. Materials and Methods: This cross-sectional qualitative study was conducted over April and May 2023 at the Andaman and Nicobar Islands Institute of Medical Sciences (ANIIMS), Port Blair, among MBBS students from the 2019-2022 batches. Students were surveyed using a semi-structured questionnaire addressing key CBME components. Open-ended questions were utilized to capture students' insights on CBME’s perceived benefits, challenges, and improvement suggestions. Thematic analysis was applied to identify recurrent themes, offering a comprehensive understanding of student experiences within the CBME framework. Results: Feedback revealed high student appreciation for foundational components, notably Basic Life Support and ethics. Recommendations for new curriculum elements included mental health support, interactive learning formats, and direct patient exposure. Common challenges cited were the extensive logbook requirements and lengthy assessments. Notably, students suggested restructuring self-directed learning (SDL) to include more guidance and advocated for case-based, scenario-driven assessments over traditional formats. Integration practices were valued, though students expressed a need for alignment between subject teachings and integrated sessions to maximize holistic learning. Conclusion: This study highlights a generally positive reception of the CBME curriculum, with specific areas identified for enhancement, including reducing administrative burdens, incorporating more practical learning activities, and adjusting assessment formats. Student feedback underscores the curriculum’s strengths in fostering competency but also suggests the need for flexibility and responsive updates to meet evolving educational demands.